Exploring the Transparency and Strength: A Comprehensive Review of Structural Glass and its Applications in Modern Structures - Mishra, Vipin (Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
Glassmaking has a long history in Lithuania. The results of archaeological investigation demonstrate that glass melting technology was already being used by individuals in the Grand Duchy of Lithuania during the XII–XIII century. The oldest Lithuanian industry that has been documented in historical sources is regarded as being this one. Currently, enthusiasm in the new glass and light flood was palpable throughout Lithuania and the rest of the world. The transparency of glass for light is one of the key properties that lends this substance its mystery. This makes this material appealing for design. In order to create load-bearing glass structures or use glass in industry, research on the resistance of glass structures to deformations on structure stability is conducted. In this essay, scholarly works on structural glass are reviewed in the literature and analysed using testing techniques. The analysis' results are included at the end of the publication, along with information on some of the structural glass fields that have not received as much attention.